Complementary Ventilation Design Method for a Highway Twin-Tunnel Based on the Compensation Concept. (14th October 2018) - Chai, Lunlei; Wang, Xing; Han, Xingbo; Song, Jing; Lei, Ping; Xia, Yongxu; Wang, Yongdong
Abstract : Based on the compensation concept, an improved method for twin-tunnel complementary ventilation design considering differences in key pollutants in the uphill and downhill tunnels was proposed. The results demonstrate that the scheme developed using the improved method is more energy efficient when the energy consumption of the interchange channel is included. Here, a larger design of air volume is allocated to the uphill tunnel, and the admissible pollutant concentration for its exits. The complementary ventilation system of the Qingniling Tunnel, Dabieshan Tunnel, and Lianghekou Tunnel was redesigned for long-term performance using the improved method, and the resulting scheme was compared to that designed using the current method in terms of the total required air volume, interchange air volume, ventilation effects, and energy consumption. The results show that these factors in improved method are significantly smaller than that of the current method with an allowable reduction of ventilation effects. Moreover, the total airflow required in the Qingniling Tunnel was reduced from 889.31 to 796.74 m 3 /s, with a decrease rate of 10.4%; the interchange air volume was reduced from 203 to 175 m 3 /s, and the estimated energy consumption was decreased from 2760 to 2065.9 kW. This represents a 26% improvement in energy efficiency. The proposed method can provide a reference for the energy efficient design of ventilation systems in extra-long highway tunnels.